Between Methodological “Ebb” and Emancipatory “Tide”: Reflecting on the “Critical” Core of Critical Discourse Studies in our own Work - Serafis, Dimitris; Bennett, Samuel (The Greek Review of Social Research, 2025)
This article offers a reassessment of the use of the “Critical” in Critical Discourse Studies (CDS). In doing so, it aims to “breathe new life” into the discussion so that the concept can be reconsidered and better understood. We return to the immanent - socio-diagnostic, retrospective- and prospective critiques, introduced by the Discourse-Historical Approach (DHA) as a valuable heuristic for considering the “Critical” in CDS. After pinpointing some limitations in contemporary CDS-oriented research, we present examples from our own research practices to show both how “critique” can be foregrounded and how different ‘‘forms’’ of critique can, and should, be combined.